Flourishing in contexts and cultures : sociocultural perspectives on fostering youth well-being - Liem, Gregory Arief D.; McInerney, D. M. 1948- (Research on sociocultural influences on motivation and learning., 2023)
"The youth of today is confronted with a myriad of challenges of living in the world that has never been more volatile, uncertain, complex, and ambiguous than ever. These multifaceted challenges compromise their well-being. Fostering the well-being of young people across sociocultural boundaries, rather than of the select groups of privileged individuals, is a timely and worthy endeavor and should not take a back seat. The advent of Positive Education, which is an educational paradigm that emphasizes the goal of developing both cognitive abilities and well-being skills in students and young people in general, has offered a promising generic approach to promoting the well-being of young people. The twin goals of Positive Education are indeed aligned with two major views of well-being: eudaimonia highlighting the importance of one's engaged pursuit of meaningful goals, and hedonia stressing the importance of one's positive emotion and life satisfaction in one's well-being. Their combo - that wellness is achieved when a person is feeling good and functioning well - has often been termed 'flourishing'. Unfortunately, scholarly discussions on sociocultural influences on flourishing or well-being and ways of promoting it have been scarce. This volume addresses such a gap in a rigorous and timely manner. International scholars from culturally diverse backgrounds put together their thoughts and ideas in their respective chapter contributions that, collectively, invite us to mindfully take into account youth's sociocultural and sociodemographic backgrounds in promoting their flourishing. This book, which embodies the 'who', 'what', when, 'where', and 'how' of youth well-being, will be extremely insightful and useful for scholars and researchers as well as policy makers and practitioners (teachers, interventionists, counsellors, youth mentors) who seek to promote the well-being of young people in their respective contexts and beyond"--